The new Jewish leaders: reshaping the American Jewish landscape - Wertheimer, Jack (Brandeis series in American Jewish history, culture, and life, 2011)
Mapping the scene: how younger Jewish adults engage with Jewish community / Jack Wertheimer -- From Jewish people to Jewish purpose: establishment leaders and their non-establishment successors / Steven M. Cohen -- Expressive, progressive, and protective: three impulses for innovative organizing among young Jews today / Steven M. Cohen -- Young Jewish leaders in Los Angeles: strengthening the Jewish people in conventional and unconventional ways / Sarah Bunin Benor -- Reimagining Jewishness: younger American Jewish leaders, entrepreneurs, and artists in cultural context / Sylvia Barack Fishman, with Rachel S. Bernstein and Emily Sigalow -- The reality of the virtual: looking for Jewish leadership online / Ari Y. Kelman -- In its own image: independent philanthropy and the cultivation of young Jewish leadership / Shaul Kelner